De vil gerne gøre en forskel, men… - Noer, Vibeke Røn; Rasmussen, Malene Damkjær; Hansen, Ditte Graversgaard (Tidsskrift for Professionsstudier, 2023)
Recruiting and retaining nurses in the profession has become increasingly challenging, and the interest in pursuing nursing education is significantly declining. In this article, we investigate the factors that motivate students to choose nursing as their field of study, as expressed in their own words, and examine what is crucial for them in terms of shaping their professional identity and envisioning a future in the profession. The analysis in this article is based on 114 self-portraits written by nursing students shortly before completing their education. The findings indicate that the nursing students are genuinely interested in the profession. They are motivated by the ambition to make a difference. However, their experiences within a healthcare system where care and nursing are under pressure present the future professionals with a difficult situation. The challenge lies in shaping their professional identity amidst the tension between ideals and a strained professional practice. One possible outcome is that the students complete their education but opt out of working as nurses. In conclusion, we argue that the healthcare system needs future nurses who dare to insist on care as a fundamental premise and as part of the nursing profession's ambition on behalf of the patient. Therefore, there is a persistent need to work on creating frameworks and conditions within the healthcare system that make this possible and that retain students in their education and later retain trained nurses in the profession.